Higher Stroke Unit Volume Associated With Improved Quality of Early Stroke Care and Reduced Length of Stay - Marie Louise Svendsen; Lars Holger Ehlers; Annette Ingeman; Søren Paaske Johnsen (2012)
Background and Purpose— Specialized stroke unit care improves outcome among patients with stroke, but it is unclear whether there are any scale advantages in costs and clinical outcome from treating a larger number of patients. We examined whether the case volume in stroke units was associated with quality of early stroke care, mortality, and hospital bed-day use. Methods— In a nationwide population-based cohort study, we identified 63 995 patients admitted to stroke units in Denmark between 2003 and 2009. Data on exposure, outcome, and covariates were collected prospectively. Comparisons were clustered within stroke units and adjusted for patient and hospital characteristics. Results— Patients in high-volume stroke units overall had a better prognostic profile than patients in low-volume stroke units. Patients in high-volume stroke units also received more processes of care in the early phase of stroke compared with patients in low-volume stroke units (unadjusted difference, 9.84 percentage points; 95% CI, 3.98–15.70). High stroke unit volume was associated with shorter length of the initial hospital stay (adjusted ratio, 0.49; 95% CI, 0.41–0.59) and reduced bed-day use in the first year after stroke (adjusted ratio, 0.79; 95% CI, 0.70–0.87). No association between volume and mortality was found. Conclusions— Patients admitted to high-volume stroke units received a higher quality of early stroke care and spent fewer days in the hospital compared with patients in low-volume units. We observed no association between volume and mortality.